THE MATRIX OF LAND TENURE PROPERTY RIGHT FOR WATER SETTLEMENT AREA - Zaini, Farah; Abdul Aziz, Shyafiena; Ali, Nurlaila; Yusuf, Adibah (PLANNING MALAYSIA, 2021)
The Land Tenure Property Right (LTPR) concept is critical for establishing ownership and rights to land or property. Land is inextricably linked to a community’s social identities, and it is critical for them to understand their rights. Water settlement areas are not included in the formal LTPR, which results in ambiguous rights, informal land tenure, and ambiguity regarding certain LTPR elements. As a result, this article will discuss the difficulties associated with LTPR in this area. The article employs a qualitative approach, with data collected via face-to-face interviews and analysed using thematic analysis. Three case studies are included, in which all of the villages are located in a water settlement area. Six challenges are identified in the context of LTPR that require revision and strengthening. By combining the general LTPR framework and the results, a Matrix of LTPR that meets the criteria in the water settlement area is produced.